Reduced Stents and Stent-Grafts for the Management of Hepatic Encephalopathy after Transjugular Intrahepatic Portosystemic Shunt Creation - Madoff, David C. (Thieme Medical Publishers, 2005)
Hepatic encephalopathy (HE) is a common complication encountered by patients after transjugular intrahepatic portosystemic shunt (TIPS) creation. Although most patients respond well to conservative medical therapy, up to 7% of patients do not and require more invasive therapeutic approaches. One option is emergent liver transplantation; however, most patients are not suitable candidates. During the past decade, various percutaneous techniques have been described that alter the hemodynamics through the TIPS by occluding it with coils or balloons or by reducing its diameter using constrained stents or stent-grafts. These endovascular techniques have produced symptomatic improvement in many patients with refractory HE, with either complete resolution or substantial reduction of HE symptoms that can be controlled with additional medical therapy. Unfortunately, despite all attempts, some patients remain incapacitated and ultimately die. Further research is necessary to improve our understanding of HE after TIPS creation so that less invasive and safer procedures can be developed to treat this difficult clinical problem.